A randomised comparison of bolus phenylephrine and ephedrine for the management of spinal hypotension in patients with severe preeclampsia and fetal compromise. (February 2018) - Dyer, R.A.; Emmanuel, A.; Adams, S.C.; Lombard, C.J.; Arcache, M.J.; Vorster, A.; Wong, C.A.; Higgins, N.; Reed, A.R.; James, M.F.; Joolay, Y.; Schulein, S.; et al.
Highlights: Randomised trial at caesarean delivery for severe preeclampsia and fetal compromise. Ephedrine and phenylephrine were compared, for spinal-induced hypotension. Umbilical arterial base excess, pH, HCO3 −, PCO2, lactate, and Apgar scores similar. Fetal acid-base status was independent of the vasopressor used. Choice of vasopressor should depend upon individual maternal haemodynamic responses. Abstract: Background: Studies in healthy patients undergoing elective caesarean delivery show that, compared with phenylephrine, ephedrine used to treat spinal hypotension is associated with increased fetal acidosis. This has not been investigated prospectively in women with severe preeclampsia. Methods: Patients with preeclampsia requiring caesarean delivery for a non-reassuring fetal heart tracing were randomised to receive either bolus ephedrine (7.5–15 mg) or phenylephrine (50–100 µg), to treat spinal hypotension. The primary outcome was umbilical arterial base excess. Secondary outcomes were umbilical arterial and venous pH and lactate concentration, venous base excess, and Apgar scores. Results: Among 133 women, 64 who required vasopressor treatment were randomised into groups of 32 with similar patient characteristics. Pre-delivery blood pressure changes were similar. There was no difference in mean [standard deviation] umbilical artery base excess (−4.9 [3.7] vs −6.0 [4.6] mmol/L for ephedrine and phenylephrine respectively; P =0.29). Mean umbilical arterial and venous pH and lactate concentrations did not significantly differ between groups (7.25 [0.08] vs 7.22 [0.10], 7.28 [0.07] vs 7.27 [0.10], and 3.41 [2.18] vs 3.28 [2.44] mmol/L respectively). Umbilical venous oxygen tension was higher in the ephedrine group (2.8 [0.7] vs 2.4 [0.62]) kPa, P =0.02). There was no difference in 1- or 5-min Apgar scores, numbers of neonates with 1-min Apgar scores <7 or with a pH <7.2. Conclusions: In patients with severe preeclampsia and fetal compromise, fetal acid-base status is independent of the use of bolus ephedrine versus phenylephrine to treat spinal hypotension.